Diseño y fabricación de un microsistema fluídico para separación de partículas por tamaño (2011)
This document shows a design methodology for microfluidic systems for flow controlled particle separation using Zweifach-Fung effect and propose to use a simplification on the flow resistance equation to improve design. Also proposes a fabrication technique and describe the fabrication and testing process of the final prototype that demonstrates that is possible to separate particles by size and liquid using a micro-structured fluid based on Alginate microcapsule fabrication technique.